Associations between Australian Early Childhood Educators' Mental Health and Working Conditions: A Cross-Sectional Study. Issue 3 (September 2015) - Corr, Lara; Cook, Kay; LaMontagne, Anthony D.; Waters, Elizabeth; Davis, Elise
EARLY CHILDHOOD EDUCATION and care quality relies on educator capacity; however, working conditions may compromise educators' mental health. This study examines associations between family day care (FDC) educators' mental health and working conditions to inform workplace mental health promotion. Three hundred and sixty-six FDC educators completed an online or written survey. In addition to this, regression analyses were used to examine relationships between educator mental health and working conditions. Although many FDC educators had low psychological distress and moderate mental wellbeing, 41.7 per cent reported psychological distress. Most educators' 'efforts' and 'rewards' were unbalanced (effort–reward imbalance [ERI] ratio) and showed high 'overcommitment' to work. Effort and overcommitment were significantly related to increased odds of psychological distress, whereas social support was associated with higher mental wellbeing. The ERI ratio had the strongest associations with educator psychological distress and mental wellbeing. As many working conditions associated with educator mental health are modifiable, this study highlights opportunities for workplace mental health promotion in FDC.